A lifetime of grammar teaching - Ellis, Rod (2012)
The author has worked as a language teacher, teacher educator, and second language acquisition (SLA) researcher for over forty years. During this time grammar has figured largely in his thinking, in part because it has traditionally been so central to language pedagogy and in part because he became fascinated with how the human mind grapples with the task of learning the grammar of a second language (L2). This professional autobiography, covering the time from the author's first teaching job in Spain up to the present, documents his development as a teacher, teacher educator, and researcher, showing how his thinking about teaching has evolved through his deepening understanding of how learners learn the grammar of a second language.